Identifikasi Stresor Akademik pada Mahasiswa Tahun Pertama - Banan Corima Adha; Shinta Mayasari; Moch. Johan Pratama (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
Problem in this research is the academic stressor high on students. The purpose of this research is to identify those academic stressor on Faculty of Teacher Training and Education UNILA students in their first year collage, year 2019/2020. This research conducted using qualitative method with 269 freshmen as the subject. The data collection was done using questionnaire. The data analysis was done through collecting online documents or answer with online survey by means of code. The results showed that the most dominant stressors are, assignment with the topic of the number of assignment and lecture process with the topic of lecture schedules irregular.Permasalahan dalam penelitian ini adalah